2016
DOI: 10.1007/s12185-016-1975-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prothrombin time tests used in the monitoring of edoxaban and their evaluation as indicators of the reversal effect

Abstract: Clinical demand for the prompt assessment of the activity of direct-acting factor Xa inhibitors in the emergency care setting is increasing. In the present study, we examined whether prothrombin time (PT) tests can serve as a clinically useful indicator of anti-factor Xa activity. In the first series, the in vitro effect of edoxaban on PT was evaluated by spiking human plasma with edoxaban and measuring PT using three different commercial PT tests. In the second series, the reversal effect of prothrombin compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Thus, examination of the figure illustrating the PT dose-response curves published by Douxfils et al indicates that the edoxaban concentration needed for a doubling of the PT baseline clotting time, according to our definition, would be close to the values we report here. Two other studies have also published PT response curves for edoxaban, without reporting any calculated CT 2 -values, and an examination of the graphs for those PT reagents used in our study it can be concluded that the edoxaban needed for doubling the basal PT clotting time is near what we report [13,16].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Thus, examination of the figure illustrating the PT dose-response curves published by Douxfils et al indicates that the edoxaban concentration needed for a doubling of the PT baseline clotting time, according to our definition, would be close to the values we report here. Two other studies have also published PT response curves for edoxaban, without reporting any calculated CT 2 -values, and an examination of the graphs for those PT reagents used in our study it can be concluded that the edoxaban needed for doubling the basal PT clotting time is near what we report [13,16].…”
Section: Discussionsupporting
confidence: 50%
“…With this knowledge about the inadequate PT and APTT sensitivities for DOACs, it cannot be advised to rely on these assays in the assessment of the anticoagulant effect [12]. However, so far, there are only few reports on the pharmacodynamic profiles of edoxaban [11,[13][14][15][16][17] and only three of these present more extensive results based on in vitro effects on routine and more specialized coagulation assays [11,13,15]. All these studies utilized pooled normal plasma spiked with edoxaban.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have assessed the performance of chromogenic assays designed to measure heparin and anti-FXa chromogenic assays with non-edoxaban-specific calibrators and controls for measuring edoxaban concentrations [19,20]. In a previous in vitro study, chromogenic assays without edoxaban-specific calibrators and controls showed good sensitivity to measuring edoxaban levels in edoxabanspiked plasma [19].…”
Section: Discussionmentioning
confidence: 99%
“…Clotting assays, such as prothrombin time (PT) and activated partial thromboplastin time (aPTT), are more widely available but are not quantitative and direct, oral FXa inhibitors have variable effects on these standard coagulation tests [11,[16][17][18]. Recent studies have suggested that some PT reagents could be useful to measure edoxaban, however, the impact of edoxaban on PT and aPTT depends on the reagents [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation